On the secrecy of multiple access wiretap channel - Ekrem, E.; Ulukus, S. (2008 46th Annual Allerton Conference on Communication, Control, and Computing, 2008)
We develop an outer bound for the secrecy capacity region of a class of multiple access wiretap channels (MAC-WT). In this class, which we call the weak eavesdropper class, each user's link to the legitimate receiver is stronger than its link to the eavesdropper. Our outer bound partially matches the achievable region in an n-letter form. In addition, a looser version of our outer bound provides close approximations to the capacity region of the Gaussian MAC-WT channel. In particular, we prove that our outer bound is within 0.5 bits/channel use of the achievable rates along the individual rates for all weak eavesdropper Gaussian MAC-WT, and within 0.5 bits/channel use in all directions for certain weak eavesdropper Gaussian MAC-WT channels.